Gaya Belajar Siswa SD Dilihat Dari Gambar Cerita Ilustrasi - Millati Askha, Ulin Nikmati; Fajrie, Nur; Amaliyah, Fitriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem in this study is that during the learning process the teacher is not very aware of the learning style of each of his students. Based on the results of observations in the classroom when learning is taking place, it was found that when the teacher explained a material, there were students in grade III who did not pay attention to the teacher's explanation. The purpose of this study was to find out about the learning styles of grade III students through illustrated story pictures at SD 1 Padurenan Kudus. Learning styles are very necessary so that the teaching and learning process can be carried out, because learning style attitudes will help them achieve their goals faster. This study uses a narrative qualitative research type. The subjects used by the researcher were 6 using data collection techniques in the form of observation, interviews, and documentation. Data analysis was carried out using the Miles and Huberman model which includes three stages: Data reduction, Data presentation, and drawing conclusions. The results of the study at SD 1 Padurenan Kudus showed that students' learning styles seen from illustrated story pictures with the category of visual learning styles showed that students tend to learn more easily when they see, the results of the pictures are neat and precise. Students in the auditory learning style category showed that students tend to listen very strongly, have strong storytelling skills, and do not like noise. Students in the kinesthetic learning style category showed that students tend to enjoy learning using body movements, or direct practice, like to try but are less neat. From the results of the study, it can be concluded that students' learning styles seen from the students' illustration story images are different. The learning styles carried out by students with visual, auditory, and kinesthetic categories are different. This research is expected to help teachers to apply various learning styles owned by each student. Therefore, teachers are strongly advised to always use visual media, such as picture stories in the learning process in order to adjust to the visual learning style, and must provide other learning methods that can facilitate auditory and kinesthetic learning styles.